Refractive Outcome After Corneal Lenticule Implantation Ex Vivo Non-Human Study - Poláchová, Martina; Netuková, Magdaléna; Sýkora, Roman; Studený, Pavel (Current eye research, 2023)
PURPOSE: To evaluate changes in corneal refractive parameters after implantation of a stromal lenticule of different thickness. We assume that the refractive outcome depends on the optical power of the used lenticule. METHODS: We conducted an ex-vivo non-human study on 33 normotonic porcine eyeballs divided into two groups, for 4D and 8D human lenticule implantation. Corneal stromal lenticules were obtained as a by-product from a laser procedure ReLEx SMILE. We evaluated corneal refractive parameters measured on Oculus Pentacam© device before and immediately after the intrastromal lenticule implantation. RESULTS: There was no statistically significant difference in corneal refractive parameters between the eyeball groups before lenticule implantation. In both groups, the intrastromal implantation in the depth of 300um led to a significant increase of central corneal pachymetry and corneal anterior steepening. In the 4D group the average central corneal pachymetry increased from 903 ± 124.59 to 1230 ± 148.99 (p = 0.0022) and in 8D group from 733.35 ± 69.60 to 1109 ± 161.64 (p = 0.0008). Induced changes in other studied parameters were not statistically significant, Kmax changed from 45.57 ± 2.78 to 72.07 ± 16.83 (p = 0.0094) and Km front from 40.72 ± 1.60 to 48.87 ± 5.83 (p = 0.0037) in 4D group and in the 8D group average Kmax increased from 42.22 ± 1.54 to 62.95 ± 12.67 (p = 0.0001) and K2 front 40.46 ± 1.64 to 51.51 ± 9.63 (p = 0.0037). There were no significant differences in refractive changes between the 4D and 8D groups after lenticule implantation. CONCLUSION: Intrastromal corneal lenticule implantation induces changes in corneal refractive parameters. In both groups, the implantation induced a significant increase of an anterior corneal steepening without any significant influence on posterior corneal flattening. Corneal lenticule implantation did not lead to any significant change of corneal astigmatism. However, in order to have more precise data for future clinical applications we need to continue with the experiments and verify the results on human corneas.
Keywords: Animals; Lasers, Excimer; Refraction, Ocular; rohovka; refrakce oka; Corneal Topography; nemoci rohovky; lasery excimerové; Cornea; lidé; prasata; Corneal Diseases; Swine; rohovková topografie; laserová chirurgie rohovky; stroma rohovky; zvířata; Corneal Surgery, Laser; Corneal Stroma; Humans